Influence of polar side chains modifications on the dual enkephalinase inhibitory activity and conformation of human opiorphin, a pain perception related peptide. Issue 22 (15th November 2015) - Rosa, Mònica; Marcelo, Filipa; Calle, Luis P.; Rougeot, Catherine; Jiménez-Barbero, Jesús; Arsequell, Gemma; Valencia, Gregorio
Graphical abstract: Abstract: The dual inhibitory action of the pain related peptide opiorphin (H-Gln-Arg-Phe-Ser-Arg-OH) against neutral endopeptidase (NEP) and aminopeptidase N (AP-N) was further investigated by a SAR study involving minor modifications on the polar side chains of Arg residues and glycosylation with monosaccharides at Ser. None of them exerted dual or individual inhibitory potency superior than opiorphin. However, the correlations deduced offer further proof for the key role of these residues upon the binding and bioactive conformational stabilization of opiorphin. NMR conformational studies on the glycopeptides suggest that they are still very flexible compounds that may attain their respective bioactive conformations.